Memanfaatkan Data Media Sosial Untuk Intelijen Kompetitif Di Era Digital - Ummi Aulia; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
The utilization of social media data has become an important strategy in acquiring competitive intelligence in the fast-paced and dynamic digital age. This study aims to investigate various aspects related to utilizing social media data for competitive intelligence. The research method used is systematic literature review, by collecting information from national journals in the last 5 years. The findings from this study are expected to provide in-depth insights into the strategies, tools, benefits, challenges, and implications of using social media data in the context of competitive intelligence